(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
Dimeria kalerii, a new species collected from the lateritic plateaus of Northern Kerala, India is described and illustrated. It is allied to Dimeria gracilis in robust habit, densely bearded nodes, lax racemes, long clavate pedicels with cupuliform apex but differs in ciliate apex of ligules, numerous racemes on the peduncles (7-32), hairy pedicels, smaller spikelets (3.8–4.2 mm), shorter cilia on the upper and lower glume, long bristly hairs at the apex of upper glume, hairy column of awns and smaller anthers (1.8–2.0 mm). Bangladesh J. Plant Taxon. 25(1): 13-18, 2018 (June)